Post-acquisition CO2 Inhalation Enhances Fear Memory and Depends on ASIC1A - Taugher, Rebecca J.; Wunsch, Amanda M.; Wang, Grace Z.; Chan, Aubrey C.; Dlouhy, Brian J.; Wemmie, John A. (Frontiers in Behavioral Neuroscience, 2021)
A growing body of evidence suggests that memories of fearful events may be altered after initial acquisition or learning. Although much of this work has been done in rodents using Pavlovian fear conditioning, it may have important implications for fear memories in humans such as in post-traumatic stress disorder (PTSD). A recent study suggested that cued fear memories, made labile by memory retrieval, were made additionally labile and thus more vulnerable to subsequent modification when mice inhaled 10% carbon dioxide (CO2) during retrieval. In light of this finding, we hypothesized that 10% CO2 inhalation soon after fear acquisition might affect memory recall 24 hours later. We found that both cue and context fear memory were increased by CO2 exposure after fear acquisition. The effect of CO2 was time-dependent, as CO2 inhalation administered 1 or 4 hours after cued fear acquisition increased fear memory, whereas CO2 inhalation 4 hours before or 24 hours after cued fear acquisition did not increase fear memory. The ability of CO2 exposure following acquisition to enhance fear memory was not a general consequence of stress, as restraining mice after acquisition did not alter cued fear memory. The memory-enhancing action of CO2 may be relatively specific to fear conditioning as novel object recognition was impaired by post-training CO2 inhalation. To explore the molecular underpinnings of these effects, we tested if they depended on the acid-sensing ion channel-1a (ASIC1A), a proton-gated cation channel that mediates other effects of CO2, likely via its ability to sense acidosis induced during CO2 inhalation. We found that CO2 inhalation did not alter cued or context fear memory in Asic1a-/- mice, suggesting that this phenomenon critically depends on ASIC1A. These results suggest that brain acidosis around the time of a traumatic event may enhance memory of the trauma, and may thus constitute an important risk factor for developing PTSD. Moreover, preventing peritraumatic acidosis might reduce risk of PTSD.